Meaningful improvement in general health outcomes with Guselkumab treatment for psoriatic arthritis: Patient-Reported Outcomes Measurement Information System-29 results from a phase 3 study - Orbai, A-M; Coates, LC; Deodhar, A; Helliwell, PS; Ritchlin, CT; Leibowitz, E; Kollmeier, AP; Hsia, EC; Xu, XL; Sheng, S; Jiang, Y; Liu, Y; et al. (Springer, 2022)
Objective The Phase 3 DISCOVER-1 study of guselkumab is the first randomized controlled trial to use Patient-Reported Outcomes Measurement Information System (PROMIS) measures to assess the effects of treatment on general health outcomes in patients with psoriatic arthritis (PsA). Methods Patients (N = 381) with active PsA were randomized 1:1:1 to guselkumab 100 mg every 4 weeks (Q4W); guselkumab 100 mg at Week 0, Week 4, then every 8 weeks (Q8W); or placebo with Week 24 crossover to guselkumab Q4W. The PROMIS-29 Profile contains four items for each of seven domains (anxiety, depression, fatigue, pain interference, physical function, sleep disturbance, and social participation) and one pain-intensity item. Raw domain scores are converted to standardized T-scores, with norms based on a US general population mean of 50 (1 standard deviation (SD) = 10). T-score changes of ≥ 5 are considered clinically meaningful. Least-squares mean PROMIS-29 T-score changes from baseline to Week 24 and Week 52 were summarized for the guselkumab and placebo groups; nominal p-values comparing results between guselkumab and placebo were calculated at Week 24 using a mixed model for repeated measures. The proportions of patients who achieved clinically meaningful improvement in PROMIS-29 T-scores were also summarized at Week 24 and Week 52; nominal p-values comparing results between guselkumab and placebo were calculated at Week 24 using the Cochran-Mantel-Haenszel test. Results In the DISCOVER-1 patient population, mean PROMIS-29 T-scores at baseline were ~ 1 SD worse for physical function and pain interference and were numerically worse for social participation, fatigue, and sleep disturbance compared with the US general population. At Week 24, mean PROMIS-29 T-scores improved in guselkumab-treated patients, approaching US population norms; T-scores continued to improve through Week 52. Significantly higher proportions of patients in both guselkumab treatment arms (31–52% across domains) had clinically meaningful improvements in pain interference, fatigue, physical function, sleep, and social participation at Week 24 versus placebo (all nominal p ≤ 0.05). Conclusion In patients with active PsA, guselkumab treatment provided clinically meaningful reductions in fatigue and pain and improvement in physical function and social participation, as measured by the PROMIS-29 Profile. These improvements were maintained through 1 year. ClinicalTrials.gov Registration number, NCT03162796; Submission date 19 May 2017.